2002
DOI: 10.1381/096089202321019594
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Endoscopy in the Management of Patients Undergoing Roux-en-Y Gastric Bypass

Abstract: Upper endoscopy is a tool which may be used by the surgeon in the preoperative and postoperative management of patients undergoing RYGBP to modify therapy, improve outcomes, and diagnose and treat postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(100 citation statements)
references
References 6 publications
1
92
0
7
Order By: Relevance
“…In a study by Schirmer et al, out of 560 patients who underwent Roux-en-Y gastric bypass at a single institution, 4.9% (26 patients) had endoscopic findings that changed or altered the operative procedure. 12 These findings included esophagitis, gastroduodenal ulcers, hiatal hernia, and gastric polyps, all findings that did not lead to cancellation of any procedure. 12 Similarly, in a study by Sharaf et al, in a cohort of 195 patients who underwent EGD prior to bariatric surgery, 42 patients had clinically important findings that ultimately resulted in either alteration of the surgical procedure (e.g., reduction of hiatal hernia) or medical management prior to operation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study by Schirmer et al, out of 560 patients who underwent Roux-en-Y gastric bypass at a single institution, 4.9% (26 patients) had endoscopic findings that changed or altered the operative procedure. 12 These findings included esophagitis, gastroduodenal ulcers, hiatal hernia, and gastric polyps, all findings that did not lead to cancellation of any procedure. 12 Similarly, in a study by Sharaf et al, in a cohort of 195 patients who underwent EGD prior to bariatric surgery, 42 patients had clinically important findings that ultimately resulted in either alteration of the surgical procedure (e.g., reduction of hiatal hernia) or medical management prior to operation.…”
Section: Discussionmentioning
confidence: 98%
“…12 These findings included esophagitis, gastroduodenal ulcers, hiatal hernia, and gastric polyps, all findings that did not lead to cancellation of any procedure. 12 Similarly, in a study by Sharaf et al, in a cohort of 195 patients who underwent EGD prior to bariatric surgery, 42 patients had clinically important findings that ultimately resulted in either alteration of the surgical procedure (e.g., reduction of hiatal hernia) or medical management prior to operation. 13 Similar findings were demonstrated in a study by Loewen et al, in which, out of 451 consecutively screened patients undergoing preoperative EGD, positive findings that lead to a change in medical management were seen in 18% of the cohort, but no patients had bariatric surgery cancelled.…”
Section: Discussionmentioning
confidence: 98%
“…Serial dilatations may be required for late strictures where there is a well-established fibrotic response. 12,20 Perforation remains a real risk (incidence of up to 2.1%), 9 particularly within 4 weeks of operation. Endoscopy should ideally be performed in the specialist bariatric unit and supportive initial management is all that is required from the emergency on-call surgeon.…”
Section: Anastomotic Stricturementioning
confidence: 99%
“…In one series, 20% of CT scans were reported as normal in patients who subsequently underwent surgery for incarcerated internal hernias. 20 The serum amylase level may be raised due to obstruction of the biliopancreatic limb which may result in the misdiagnosis of pancreatitis. 2 The on-call surgeon should operate if signs of intestinal necrosis are present (pain, acidosis, lactate rise).…”
Section: Internal Herniasmentioning
confidence: 99%
“…In this series, the most common finding was hiatal hernia (40%) that required crural repair or reduction of the hernia. Schirmer et al [86], in another retrospective study, reported that the incidence of postoperative marginal ulcers was significantly lower in the group of patients who were preoperatively tested for the presence of H. pylori and treated if positive, as compared to those in whom no preoperative testing was performed (2.4% as compared to 6.9%, p < 0.05).…”
Section: Types Of Surgical Proceduresmentioning
confidence: 99%